Parenting Styles and Their Influence on the Learning Discipline of Grade V Students at SD Negeri I Marawali - Nia Kartika; Madi Madi; La Jusu; Abdul Rahim (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the application of parenting styles on the learning discipline of Grade V students at SD Negeri 1 Marawali. The focus of this research includes the types of parenting styles used by parents (authoritarian, democratic, and permissive) and their impact on students’ disciplinary behavior in the learning context. A descriptive qualitative approach was employed, with data collection techniques including observation, interviews, and documentation. The research population consisted of 26 individuals: 13 Grade V students and their 13 parents. The findings indicate that the dominant parenting style used by parents is the democratic style, followed by permissive and authoritarian styles. Students’ learning discipline was observed through several indicators such as punctuality in arriving at school, adherence to learning activities, and compliance with assignments and school rules. It was found that students raised with a democratic parenting style tend to exhibit better learning discipline compared to those with other parenting styles. This study highlights the crucial role of parents in shaping children’s discipline from an early age through the application of appropriate and consistent parenting strategies.